2020
DOI: 10.1002/ecs2.3181
|View full text |Cite
|
Sign up to set email alerts
|

Population‐level monitoring of stress in grizzly bears between 2004 and 2014

Abstract: Grizzly bears (Ursus arctos) in west‐central Alberta occupy an increasingly human‐dominated landscape. Natural resource extraction activities are hypothesized to increase stress in animals that reside in such changing landscapes by influencing habitat and resource availability. Our study aimed to determine whether stress, represented by hair cortisol concentration (HCC), was associated with variables related to landscape conditions in a population that increased by 7% annually from 2004 to 2014. Hair samples (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 78 publications
0
18
0
Order By: Relevance
“…Cortisol levels above baseline circadian and circannual levels or population means are commonly used to infer adaptive responses to an external stressor ( Romero, 2004 ; Ware et al , 2013 ; Wilson et al , 2020 ) and, increasingly, potentially maladaptive responses to anthropogenic stressors ( Van Meter et al , 2009 ). Direct comparison of cortisol levels among studies is not possible because of variation in hormone analysis methods and differences in baseline levels between populations.…”
Section: Discussionmentioning
confidence: 99%
“…Cortisol levels above baseline circadian and circannual levels or population means are commonly used to infer adaptive responses to an external stressor ( Romero, 2004 ; Ware et al , 2013 ; Wilson et al , 2020 ) and, increasingly, potentially maladaptive responses to anthropogenic stressors ( Van Meter et al , 2009 ). Direct comparison of cortisol levels among studies is not possible because of variation in hormone analysis methods and differences in baseline levels between populations.…”
Section: Discussionmentioning
confidence: 99%
“…Procedures for carrying out landscape extractions were followed as previously described 63 . Briefly, we generated both dynamic (annually varying) and static geo-spatial variables from remotely sensed data for 2013–2019.…”
Section: Methodsmentioning
confidence: 99%
“…We predicted that variables related to anthropogenic disturbance would be associated with increased expression of proteins related to stress, as previous studies have demonstrated a relationship between human use on the landscape and long term stress in grizzly bears 52 , 63 . Increased reproductive success has been associated with increased food resources in several species and in particular, primary habitat for grizzly bear reproduction has been shown to have specific land cover attributes 58 , 62 .…”
Section: Introductionmentioning
confidence: 99%
“…Commercially available EIA kits provide laboratories with easy-to-follow procedures and the majority of materials needed to complete the assay. Oxford Biomedical Research (Oxford, Michigan, USA) manufactures a commonly used EIA kit for the hormone cortisol (EA65 Cortisol EIA kit), which has been used to measure cortisol concentration in the hair of wildlife [2] , [3] , [4] , [5] , [6] . The use of this EIA kit has previously been validated in our laboratory for the quantification of cortisol in wildlife hair, and has shown excellent performance characteristics (accuracy and precision) [2 , 3 , 7] .…”
Section: Methods Detailsmentioning
confidence: 99%
“…As technology continues to develop, laboratories are often faced with changes to protocols, such as antibody replacement or changes in the concentration of antibody, which can lead to differences in EIA sensitivity [9] , [10] , [11] . These changes become especially important when monitoring hormone concentrations in many individuals or populations over long periods of time (i.e., years to decades), which is often the goal in wildlife studies [6] . The antibody for the cortisol EIA kit by Oxford Biomedical was replaced in 2014, which resulted in differences in cross reactivity and standard curve concentrations compared to the previous antibody ( Table 1 ).…”
Section: Methods Detailsmentioning
confidence: 99%